Perkembangan Jiwa Beragama Pada Anak Usia 2-4 Tahun - Ramadan Lubis; Putri Hasanah Harahap; Nadia Salsabila; Yesa Dwi Khairani; Fitri Ana Daulay; Azmi Oktari Harahap; Nur Nani Siagian (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
The development of a religious spirit in children is an early development even before childhood and they receive religious education. This research aims to find out how the religious spirit develops in children aged 2-4 years. This research is a type of research that uses qualitative methods and involves library study methods. Data collection techniques used interview methods and literature research. This research discusses the religious spirit or development of the religious spirit in children aged 2-4 years. The results of this research show that the children interviewed who were 4 years old had good development of their religious spirit and already knew a lot about religion from simple things.